(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The use of fiber board is increasing due to limited supply of timer wood. This study investigated the suitability of medium density fiber board (MDF) made from rubber wood for household and industrial use. Rubber wood was collected from Bangladesh Forest Development Corporation (BFIDC), Chattogram. Single layer fiber boards were fabricated by five different densities, such as 700, 725, 750, 775 and 800 kgm-3. The mechanical and physical properties of medium density fireboards fabricated by rubber wood fiber as a raw material and urea formaldehyde as a resin were studied. The performance of composite was evaluated by its mechanical and physical properties. Experimental investigation indicated that the mechanical strength of medium density fiber board such as modulus of rupture (MOR) and tensile strength increased with increasing board density. The bending strength (188-234kgcm-2) passed the Indian, German and British standard while the tensile strength (4.20-4.70kgcm-2) passed the German and British Standard specification. The research concluded that 800kgm-3 fiber board made from rubber wood had the best modulus of rupture (234 kgcm-2) and the highest tensile strength (4.70 kgcm-2) among all other single layer medium density fiber boards. Bangladesh J. Agril. Res. 46(2): 203-209, June 2021